The challenges of alternative dispute resolution for Islamic Finance in Malaysia - Nur Khalidah Dahlan; Mohd Rizal Palil (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia’s authority on Islamic Finance is recognized worldwide. Islamic finance benefits and advantages have helped to develop many countries regardless of religions or communities. However, many countries such as United Kingdom, UEA, Asian countries that are adopting Islamic finance will bound to encounter some disputes through the Islamic finance application. This article provides some insights on the judgment of Malaysian court (Muamalat court) and seek to evaluate the best way for Malaysia to approach the issues. Issues such as whether financial products offered by Islamic banking institutions are Sharia compliant and whether the terms and conditions of the contracts embodied in such products are fair to all parties involved. It is suggested that while a Malaysian court have long solved many disputes through its application, it is still possible for future disputes be resolved using Alternative Dispute Resolution.